2010
DOI: 10.1007/s12126-010-9065-0
|View full text |Cite
|
Sign up to set email alerts
|

Responding and Intervening in Elder Abuse and Neglect

Abstract: This paper will provide an overview and discussion of the causal and risk factors relating to elder abuse, together with some of the interventions that might be used. The issues and developments that have occurred will be briefly explored. Over the last 10 years there has been increasing global recognition of the abuse and neglect of vulnerable older adults as a social problem in need of attention. A number of European countries have been working in this area but are at different stages of development. The ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In fact, Penhale (2010) asserts that past relationships is a sensitive research topic and therefore difficult to research.…”
Section: Past Relationships Between Older Person and Caregivermentioning
confidence: 99%
“…In fact, Penhale (2010) asserts that past relationships is a sensitive research topic and therefore difficult to research.…”
Section: Past Relationships Between Older Person and Caregivermentioning
confidence: 99%
“…International Network for the Prevention of Elder Abuse, World Elder Abuse Awareness Day, Abuse and Neglect of the Elderly discussion on abuse showed that only 15-16% of domestic abuse as well as other forms of aggressive behaviours have been recognized -majority of older victims are still unknown. Critical assessment of the spread of awareness of mistreatment depends on understanding of what constitutes elder mistreatment (Tobiasz-Adamczyk 2009, Penhale 2010.…”
Section: Dilemmas and Intractable Problemsmentioning
confidence: 99%
“…[4] Much research in recent years has focused on the prevalence of elder abuse, [4][5][6][7] attitudes and knowledge of professionals regarding elder abuse, [8][9][10] assessment tools to rate elder abuse [11,12] and knowledge of risk factors relating to elder abuse. [13,14] Although many researchers have addressed the need for professional education, there is little research on the development and use of educational programmes. The WHO states that "education involves not only teaching new information but also changing attitudes and behavior, and is thus a fundamental preventive strategy".…”
Section: Introductionmentioning
confidence: 99%